Análise econômica do direito tributário: fundamentos econômicos para a certeza e previsibilidade na aplicação da norma tributária - Comunello, Luciano Nardi (Universidade do Vale do Rio dos Sinos, 2015)
This research presents, in a more general sense, the Economic Analysis of Tax Law and, in a more specific way, the economy contributions on the assertion of legal certainty in the application of tax rules. It is an exploratory research, based on eminently literature review on the covered topics. It initially seeks the professional literature in order to elucidate the contribution of economics to the study of Law, in general, and Tax Law, in particular. The following chapter addresses the issue of legal certainty as a rule principle, and its contents on certainty and stability on rules application. The juridic literature elucidates the concepts that present the normative prevalence of legal certainty over other rules of the juridic order. After exploring the normative approach, it goes through the consequentialist approach to the theme, settings relations between information obtained with the economics bibliographic research and Law. Thus, it explicits the relation between the concept of uncertainty and transaction costs. The last chapter presents the results of the literature research on decision theory, specially the expected utility theory, and the study of individual behavior towards risk situations. Based on the expected utility theory it proposes a decision model on the application of tax rule in a scenario of legal certainty and another model on the application of tax rule in a scenario of legal uncertainty. From the models construction it is possible to conclude that certainty in the application of tax law encourages the choice to pay taxes, while the uncertainty in the application of the rule encourages a greater number of people to seek profit by tax evasion.
Keywords: Análise Econômica do Direito Tributário; Segurança jurídica; Teoria da Decisão; Teoria da utilidade esperada; Comportamento frente ao risco; Insegurança jurídica e incentivo à evasão fiscal; Economic Analysis of Tax Law; Legal certainty; Decision Theory; Expected Utility Theory; Behavior Towards Risk; Legal Uncertainty and Tax Evasion Encouragement